THE USAGE OF ARTICLES IN ENGLISH - Muxammadiyev Aziz Shavkatovich, Suyunov Javohir Shokir o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
To be fluent in English, to make the right sentences while speaking, to translate a work or an article correctly, in short, to make the information you want to convey understandable and correct, English perfect knowledge of grammar is required. In this article, you will learn more about what an article is in English and when to use it. The topic of the article may seem easy to us, but it is the topic that requires the most detailed study in English grammar.